Pola Komunikasi Organisasi Pimpinan Wilayah Muhammadiyah Bengkulu - Ras man (Fakultas Agama Islam Universitas Muhammadiyah Bengkulu, 2020)
COMMUNICATION PATTERNS OF MUHAMMADIYAH REGIONAL LEADERSHIP ORGANIZATION OF BENGKULU BY: RASMANMuhammadiyah University of Bengkulu,Email: rasman@umb.ac.id ABSTRACT Muhammadiyah is one of the community organizations (mass organizations) engaged in religious and social fields. The communication process within the Muhammadiyah organization is also the most important part in communication activities to achieve organizational goals. Through this communication process, we need a communication pattern that can deliver messages with the right target and can run effectively. The purpose of this study was to find out how the Circle Communication Pattern, Wheel Communication Pattern, Y Communication Pattern, Chain Communication Pattern, used between the Muhammadiyah Bengkulu Leadership with the Assembly and Institution. The method used in this study was a descriptive qualitative method. The data was collected by observation, interviews and documentation. The theory used was Joseph A Devito communication patterns. In the theory there are five theories of communication patterns namely circle patterns, wheel patterns, Y patterns, chain patterns and patterns of all channels or star patterns. The results obtained that the wheel pattern used by the Muhammadiyah Bengkulu Regional Leadership when communicating with assemblies and institutions. Keywords: Pattern, Communication, Organization, Muhammadiyah